1974
DOI: 10.1107/s0567740874004365
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of bisanilinebis(dimethylglyoximato)cobalt(III) chloride

Abstract: Crystals of the title compound, [Co(Hdmg)z(aniline)z]Cl (Hdmg is the dimethylglyoximato mono-anion), are monoclinic, space group C2/c with a=27.44 (1), b=6.32 (1), c=17.72 (1)A.; fl= 129.7 (1) ° and Z=4. The structure has been solved by Patterson and Fourier methods and refined by block-diagonal least squares (final R=4.3 %). The nitrogen atoms of two aniline molecules coordinate to cobalt in an octahedral axial position with respect to the plane of the chelate dimethylglyoximatocobalt(IlI) system. The approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

1976
1976
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
2
Order By: Relevance
“…14(1) 9(1) N12 0.2047 (3) 0.6050 (4) 0.5653 (3) 20(1) 35 (2) 30(1) 5( 1) 5 (1) 1) 40 (1) 26 (1) 18(1) 17(1) 023 0.1713 (4) 0.0375 (4) 0.0011 (4) 61 (2) 60 ( 2) 53 (2) 23 (1) 21 (1) 52( 1) 50 (1) 23 (1) 21 (1) 19(1) 027 1.10 (4) 1.86 (4) 0.97 (4) 2.44 (4) 1.02 (4) 1.98 (4) 0.96 (3) 2.35 (3) 0.96 (3) 2.08 (3) 1.09 (4) 1.81 (5) 0.95 (4) 2.19 (4) 0.98 (4) 2.07 (4) 1.07 (4) 2.20 (4) 0.86 (4) 2.14 (4) 0.93 (5) 2. 27 (5) 0.98 (3) 2.11 (3) 0.94 (4) 2.59 (4) 0.84 (4) 1.97 (4) 0.87 (5) 2.37 (6) 0.67 (5) 2.14 (6) 0.92 (4) 1.79 (4) 1.10 (6) 1.69 (6) 0.99 (3) 1.90 (4) 0.66 (6) 2.23 (6) 0.93 (5) 1.84 (5) 0.93 (5) 2.24 (5) 0.86 (3) 1.90 (5) 0.74 (4) 2.57 (5) 2.926 (4) 161 (3) 3.318 (4) 149 (3) 2.936 (5) 154 (3) 3.011 (4) 125 (3) 2.995 (4) 158 (3) 2.889 (4) 167 (4) 3.070 (4) 154 (3) 3.011 (4) 161 (3) 3.229 (4) 161 (3) 2.959 (5) 157 (3) 3.204 (5) 176 (3) 3.069 (5) 165 (3) 3.449 (4) 152 (3) 3.307 (4) 2.768 (4) 157 (4) 3.181 (4) 156 (4) 2.770 (5) 157 (6) 2.651 (5) 153 (4) 2.720 (4) 152 (4) 2.849 (5) 159 (4) 2.743 (5) 135 (5) 2.767 (4) 172 (4) 3.043 (4) 145 (4) 3.533 (4) 169 (4) 3.293 (4) 169 (5) H19 could not be located but is probably directed toward Cl.…”
Section: Resultsunclassified
“…14(1) 9(1) N12 0.2047 (3) 0.6050 (4) 0.5653 (3) 20(1) 35 (2) 30(1) 5( 1) 5 (1) 1) 40 (1) 26 (1) 18(1) 17(1) 023 0.1713 (4) 0.0375 (4) 0.0011 (4) 61 (2) 60 ( 2) 53 (2) 23 (1) 21 (1) 52( 1) 50 (1) 23 (1) 21 (1) 19(1) 027 1.10 (4) 1.86 (4) 0.97 (4) 2.44 (4) 1.02 (4) 1.98 (4) 0.96 (3) 2.35 (3) 0.96 (3) 2.08 (3) 1.09 (4) 1.81 (5) 0.95 (4) 2.19 (4) 0.98 (4) 2.07 (4) 1.07 (4) 2.20 (4) 0.86 (4) 2.14 (4) 0.93 (5) 2. 27 (5) 0.98 (3) 2.11 (3) 0.94 (4) 2.59 (4) 0.84 (4) 1.97 (4) 0.87 (5) 2.37 (6) 0.67 (5) 2.14 (6) 0.92 (4) 1.79 (4) 1.10 (6) 1.69 (6) 0.99 (3) 1.90 (4) 0.66 (6) 2.23 (6) 0.93 (5) 1.84 (5) 0.93 (5) 2.24 (5) 0.86 (3) 1.90 (5) 0.74 (4) 2.57 (5) 2.926 (4) 161 (3) 3.318 (4) 149 (3) 2.936 (5) 154 (3) 3.011 (4) 125 (3) 2.995 (4) 158 (3) 2.889 (4) 167 (4) 3.070 (4) 154 (3) 3.011 (4) 161 (3) 3.229 (4) 161 (3) 2.959 (5) 157 (3) 3.204 (5) 176 (3) 3.069 (5) 165 (3) 3.449 (4) 152 (3) 3.307 (4) 2.768 (4) 157 (4) 3.181 (4) 156 (4) 2.770 (5) 157 (6) 2.651 (5) 153 (4) 2.720 (4) 152 (4) 2.849 (5) 159 (4) 2.743 (5) 135 (5) 2.767 (4) 172 (4) 3.043 (4) 145 (4) 3.533 (4) 169 (4) 3.293 (4) 169 (5) H19 could not be located but is probably directed toward Cl.…”
Section: Resultsunclassified
“…H (16) [C( 14)] 0.87 ( 8) 228 ( 11) 734 ( 8) 456 (6) 8.6 (2.2) H (21) [C(23)J 0.86 ( 10) 414 (12) 59( 8)…”
Section: H(5)[c(5)]unclassified
“…where NioxH is monoanion of 1,2-cyclohexanedionedioxime and An -aniline) [44], the crystallization water molecules and external anions form a supramolecular H-bonds system. All anions used in this study are able to form hydrogen bonds because of the high electronegativity of atoms, which they contain.…”
Section: Resultsmentioning
confidence: 99%
“…Aniline molecules do not contain functional groups which could cause a different orientation of these ligands through the formation of hydrogen bonds (NH 2 group of the aniline molecule is coordinated to the central atom and does not infl uence in any case the steric factor of the benzene ring, and for this reason it was excluded from the study). However, besides π-π interactions which are formed between the benzene ring and the metallocycle of the equatorial plane, in some cases week hydrogen bonds such as C-H···F or C-H···O were observed [44]. it was observed that anions and water molecules form their own supramolecular system under a complicated system of hydrogen bonds (Fig.…”
Section: Resultsmentioning
confidence: 99%